Ablation failure behavior analysis of rudder made of D6AC steel in wind tunnel environment. (July 2019) - Feng, Shijie; Sun, Dongbai; Wang, Wenrui; Yu, Hongying; Zhao, Fei; Liu, Fuhai; Wang, Qi
Abstract: The ablation failure behavior of rudder made of D6AC steel has been investigated under different total temperatures (2300 K, 2400 K and 2500 K) in wind tunnel environment at Mach 5. The results showed that ablation was trace before severe ablation occurrence, and deterioration of mechanical properties caused by grain boundary premelting was primarily responsible for severe ablation failure. A phenomenon was observed that the average linear ablation rates after severe ablation occurrence for the 17 mm at the front of the specimens (ALARASAO) decreased with the increase of total temperatures, which resulted from less heat accumulation caused by pneumatic heating at higher total temperatures with less heat accumulation time. Graphical abstract: Unlabelled Image Highlights: Ablation failure behavior of rudder made of D6AC steel was investigated in wind tunnel environment. Deterioration of mechanical properties was primarily responsible for severe ablation failure. Average linear ablation rates after severe ablation occurrence decreased with the increase of total temperatures. Fluid-temperature-solid coupling analysis was conducted to illustrate the recession phenomenon.